2018
DOI: 10.5006/3092
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Hydrogen Permeation in H2S Environments with O2 Contamination, Part 2: Impact of H2S Partial Pressure

Abstract: Materials selection in the oil and gas industry relies on engineering standards, such as NACE TM0177 and NACE TM0284, which stipulate that oxygen contamination should be avoided during materials testing in H 2 S-containing media. In this second paper, as part of a series of articles that evaluates how traces of oxygen modify the corrosion of pure iron and hydrogen permeation across iron membranes in H 2 Scontaining solutions, the impact of changing the H 2 S partial pressure from 100 kPa to 0.1 kPa was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Furthermore, Liu et al have observed the formation of troilite, atop mackinawite, with long aging times. 29 By comparison, the exposure of X52 to identical H 2 S-saturated NACE A solution (1 bar), 30 or the exposure of pure Fe to unbuffered H 2 S-saturated brine for a similar period of time only led to the development of mackinawite, 8 in line with another literature reports in similar nonbuffered conditions.…”
Section: ; 26supporting
confidence: 83%
“…Furthermore, Liu et al have observed the formation of troilite, atop mackinawite, with long aging times. 29 By comparison, the exposure of X52 to identical H 2 S-saturated NACE A solution (1 bar), 30 or the exposure of pure Fe to unbuffered H 2 S-saturated brine for a similar period of time only led to the development of mackinawite, 8 in line with another literature reports in similar nonbuffered conditions.…”
Section: ; 26supporting
confidence: 83%